Capturing light in the mirror: A scientific journey through the history of daguerreotypy and its pioneers - Quintero Balbas, Diego; Benassi, Laura; Striova, Jana (Il Colle di Galileo, 2025)
Daguerreotypes are the first widely disseminated photographic process made public in the first half of the 19th century. Their invention and development are closely related to a network of scientists, primarily physicists and chemists, whose interest in light and its phenomena significantly contributed to the advancement of photographic techniques. This contribution traces the history of daguerreotypy through the figures of these scientists, opening a window onto a fascinating chapter of the history of science.